PENETRATION OF PLATES AND PLUMES THROUGH THE MANTLE TRANSITION ZONE - Davies G.F. (My University, 1995)
Reliable evaluations of whether a phase transformation boundary with a negative Clapeyron slope will cause mantle convection to be stratified will require models to include good simulations of plates and plumes. Here numerical models of mantle convection are presented that incorporate reasonable simulations of subducting lithospheric plates and good simulations of rising low-viscosity mantle plumes, as well as being carefully scaled to other first-order parameters of the mantle. The models show that subducting plates and plume heads penetrate a phase transformation barrier more readily than does flow in constant viscosity convection models in which plates and plumes are poorly simulated. Plates can penetrate a larger magnitude of the Clapeyron slope than plume heads, with plume tails the least able to penetrate. These results, together with recent laboratory results on Clapeyron slopes and observational evidence that even weak plume tails reach the surface, suggest that subducting plates usually are not strongly resisted by this mechanism, and that putative episodes of mantle overturn would be much less dramatic than in some recent constant-viscosity models.